Research of the process of vacuum cooling of bread - Kozak, Oleksandr; Telychkun, Ivanna; Desyk, Mykola; Telychkun, Volodymyr (My University, 2020)
The article presents the results of research of the vacuum-evaporating method of cooling bread. It is established that the duration of cooling bread, weighing 0.5 kg, is reduced from 60-90 minutes, when cooling products in an environment with a temperature of 20ºC and relative humidity φ = 75%, up to two minutes. The influence of regime parameters of vacuum cooling process on humidity and bread temperature is investigated. The magnitude of the vacuum and the intensity of its creation has an important impact on the quality of bread. To ensure the bread temperature within 25 ° C, it is necessary to create a vacuum value of 97 kPa. The mode of creation of vacuum at which integrity of samples which were investigated and high intensity of cooling is provided is offered

У статті наведено результати дослідження вакуумно-випарного способу охолодження хліба. Встановлено, що тривалість охолодження хліба масою 0,5 кг скорочується з 60-90 хвилин при охолодженні виробів у середовищі з температурою 20ºС і відносною вологістю φ = 75% до двох хвилин. Досліджено вплив режимних параметрів процесу вакуумного охолодження на вологість і температуру хліба. Величина вакууму та інтенсивність його створення має важливий вплив на якість хліба. Для забезпечення температури хліба в межах 25°С необхідно створити розрідження 97 кПа. Запропоновано режим створення вакууму, при якому забезпечується цілісність досліджуваних зразків та висока інтенсивність охолодження
Keywords: випікання хліба; вакуум-випарне охолодження; кафедра машин і апаратів харчових та фармацевтичних виробництв; baking bread; vacuum-viparne cooling